Road safety: serious injuries remain a major unsolved problem. Issue 6 (11th September 2017) - Beck, Ben; Cameron, Peter A; Fitzgerald, Mark C; Judson, Rodney T; Teague, Warwick; Lyons, Ronan A; Gabbe, Belinda J
Abstract: Objective: To investigate temporal trends in the incidence, mortality, disability‐adjusted life‐years (DALYs), and costs of health loss caused by serious road traffic injury. Design, setting and participants: A retrospective review of data from the population‐based Victorian State Trauma Registry and the National Coronial Information System on road traffic‐related deaths (pre‐ and in‐hospital) and major trauma (Injury Severity Score > 12) during 2007–2015. Main outcomes and measures: Temporal trends in the incidence of road traffic‐related major trauma, mortality, DALYs, and costs of health loss, by road user type. Results: There were 8066 hospitalised road traffic major trauma cases and 2588 road traffic fatalities in Victoria over the 9‐year study period. There was no change in the incidence of hospitalised major trauma for motor vehicle occupants (incidence rate ratio [IRR] per year, 1.00; 95% CI, 0.99–1.01; P = 0.70), motorcyclists (IRR, 0.99; 95% CI, 0.97–1.01; P = 0.45) or pedestrians (IRR, 1.00; 95% CI, 0.97–1.02; P = 0.73), but the incidence for pedal cyclists increased 8% per year (IRR, 1.08; 95% CI; 1.05–1.10; P < 0.001). While DALYs declined for motor vehicle occupants (by 13% between 2007 and 2015), motorcyclists (32%), and pedestrians (5%), there was a 56% increase in DALYs for pedal cyclists. The estimated costs of health loss associated with road traffic injuries exceeded 14 billion during 2007–2015, although the cost per patient declined for all road user groups. Conclusions: As serious injury rates have not declined, current road safety targets will be difficult to meet. Greater attention to preventing serious injury is needed, as is further investment in road safety, particularly for pedal cyclists.